LEGISLASI HUKUM EKONOMI SYARI’AH DI INDONESIA (Ahkam: Jurnal Hukum Islam, 2024)
Legislation is a process that takes place in legislative institutions, namely the creation and promulgation of laws and regulations. Islamic legal material can be included into the legislative process through a positivization mechanism. One of the sub-fields in the study of Islamic law is sharia economic law. Sharia economic law is a subsystem in the Islamic legal system which has experienced significant development over time. Therefore, there is a need for legal positivization through legal legislation efforts. The position of sharia economic law in the legal system has been implemented, as seen from the many institutions or economic institutions that are based on sharia values. There are several regulations in the field of sharia economic law that have been made by legislative institutions which originate from Islamic legal norms.
Keywords: Legislation; Sharia Economic Law; Regulation in Indonesia